STRUCTURE AND LITHO-FACIAL FEATURES OF THE QALA SUITE DEPOSITS OF THE ZYKH-HOVSAN AREA ACCORDING TO 3D SEISMIC AND WELL LOGGING DATA - AKHMEDOV, Tofik; KHALILOVA, Lala (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. A detailed study of the geological structure and litho-facial features of the deposits of the Pliocene productive series based on 3D seismic and Well Logging data is of great practical importance, as the main share of hydrocarbons produced in Azerbaijan occurs in these deposits. The purpose of the research was to identify the features of the geological structure of the Zykh-Hovsan area, study the litho-facial properties deposits of the Qala Suite of the productive series, identify and study the deposits within the 3 formations of the Qala Suite based on a joint analysis of 3D seismic and Well Logging (WL) data. Methods. Structural mapping based on seismic data was chosen as the main research method. In studying the Qala part of the section, seismogeological, seismostratigraphic and paleogeomorphological analyzes were also carried out. Results. According to the contour of anomalies of lowered and enhanced values of medium amplitudes (reflected waves) RW of the SH (seismic horizons) and maps of temporary thicknesses, and in some cases along faults, in different parts of the Zykh-Hovsan area within the QaS formations, deposits were identified, their size and area were determined. Effective and oil saturated thicknesses were determined for each deposit. According to the last interval of testing and perforation in the wells drilled in the study area, as well as along the top of the water-saturated reservoir and along the bottom of the oil-saturated reservoir, absolute marks (a.m.) of oil-water contacts of the identified deposits were established. The nature of saturation was determined using WL data. The type of each deposit was also determined in the process of research. Conclusions. In Qala deposits developed in the research area, the following were identified: one perspective trap in the QaS-3 formation, two traps in the QaS-2 formation and one trap in the QaS-1 formation at the Zykh field, which were identified on the basis of paleo-geomorphological features where it is suspected that the conditions for accumulation of sandy material are advantageous.